Deletion of the myeloid endothelin-B receptor confers long-term protection from angiotensin II-mediated kidney, eye and vessel injury - Guyonnet, Léa; Czopek, Alicja; Farrah, Tariq E; Baudrie, Véronique; Bonnin, Philippe; Chipont, Anna; Lenoir, Olivia; Sennlaub, Florian; Roubeix, Christophe; Webb, David J; Kluth, David C; Bailey, Matthew A; et al. (Kidney international, 2020)
The endothelin system may be an important player in hypertensive end-organ injury as endothelin-1 increases blood pressure and is pro-inflammatory. The immune system is emerging as an important regulator of blood pressure and we have shown that the early hypertensive response to angiotensin-II infusion was amplified in mice deficient of myeloid endothelin-B (ETB) receptors (LysM-CreEdnrblox/lox). Hypothesizing that these mice would display enhanced organ injury, we gave angiotensin-II to LysM-CreEdnrblox/lox and littermate controls (Ednrblox/lox) for six weeks. Unexpectedly, LysM-CreEdnrblox/lox mice were significantly protected from organ injury, with less proteinuria, glomerulosclerosis and inflammation of the kidney compared to controls. In the eye, LysM-CreEdnrblox/lox mice had fewer retinal hemorrhages, less microglial activation and less vessel rarefaction. Cardiac remodeling and dysfunction were similar in both groups at week six but LysM-CreEdnrblox/lox mice had better endothelial function. Although blood pressure was initially higher in LysM-CreEdnrblox/lox mice, this was not sustained. A natriuretic switch at about two weeks, due to enhanced ETB signaling in the kidney, induced a hypertensive reversal. By week six, blood pressure was lower in LysM-CreEdnrblox/lox mice than in controls. At six weeks, macrophages from LysM-CreEdnrblox/lox mice were more anti-inflammatory and had greater phagocytic ability compared to the macrophages of Ednrblox/lox mice. Thus, myeloid cell ETB receptor signaling drives this injury both through amplifying hypertension and by inflammatory polarization of macrophages.The endothelin system may be an important player in hypertensive end-organ injury as endothelin-1 increases blood pressure and is pro-inflammatory. The immune system is emerging as an important regulator of blood pressure and we have shown that the early hypertensive response to angiotensin-II infusion was amplified in mice deficient of myeloid endothelin-B (ETB) receptors (LysM-CreEdnrblox/lox). Hypothesizing that these mice would display enhanced organ injury, we gave angiotensin-II to LysM-CreEdnrblox/lox and littermate controls (Ednrblox/lox) for six weeks. Unexpectedly, LysM-CreEdnrblox/lox mice were significantly protected from organ injury, with less proteinuria, glomerulosclerosis and inflammation of the kidney compared to controls. In the eye, LysM-CreEdnrblox/lox mice had fewer retinal hemorrhages, less microglial activation and less vessel rarefaction. Cardiac remodeling and dysfunction were similar in both groups at week six but LysM-CreEdnrblox/lox mice had better endothelial function. Although blood pressure was initially higher in LysM-CreEdnrblox/lox mice, this was not sustained. A natriuretic switch at about two weeks, due to enhanced ETB signaling in the kidney, induced a hypertensive reversal. By week six, blood pressure was lower in LysM-CreEdnrblox/lox mice than in controls. At six weeks, macrophages from LysM-CreEdnrblox/lox mice were more anti-inflammatory and had greater phagocytic ability compared to the macrophages of Ednrblox/lox mice. Thus, myeloid cell ETB receptor signaling drives this injury both through amplifying hypertension and by inflammatory polarization of macrophages.